Recent Development of Probiotic Bifidobacteria for Treating Human Diseases - Chen, Jun; Chen, Xinyi; Ho, Chun Loong (Frontiers in Bioengineering and Biotechnology, 2021)
Bifidobacterium is a non-spore-forming, Gram-positive, anaerobic probiotic actinobacterium and commonly found in the gut of infants and the uterine region of pregnant mothers. Like all probiotics, Bifidobacteria confer health benefits on the host when administered in adequate amounts, showing multifaceted probiotic effects. Examples include B. bifidum, B. breve, and B. longum, common Bifidobacterium strains employed to prevent and treat gastrointestinal disorders, including intestinal infections and cancers. Herein, we review the latest development in probiotic Bifidobacteria research, including studies on the therapeutic impact of Bifidobacterial species on human health and recent efforts in engineering Bifidobacterium. This review article would provide readers with a wholesome understanding of Bifidobacteria and its potentials to improve human health.